Polyphenol Rich Forsythia suspensa Extract Alleviates DSS-Induced Ulcerative Colitis in Mice through the Nrf2-NLRP3 Pathway - Limin Chao; Jin Lin; Jing Zhou; Hongliang Du; Xiaoli Chen; Mengjie Liu; Qian Qu; Weijie Lv; Shining Guo (MDPI AG, 2022)
This study systematically evaluated the effect of Forsythia suspensa extract on dextran sodium sulfate (DSS)-induced ulcerative colitis (UC) and determined its mechanism of action. The results showed that Forsythia suspensa extract significantly inhibited DSS-induced UC in mice. In vivo mechanistic studies revealed that Forsythia suspensa extract relieved the symptoms of colitis by enhancing antioxidant activity and inhibiting pyroptosis. Further in vitro experiments on the mechanism of Forsythia suspensa showed that it reduced the level of reactive oxygen species (ROS) in J774A.1 cells. We found that Forsythia suspensa extract enhanced cellular antioxidation activity and inhibited pyroptosis. After silencing NLRP3, it was found to play an important role in pyroptosis. In addition, after Nrf2 was silenced, the inhibitory effect of Forsythia suspensa extract on cell pyroptosis was eliminated, indicating an interaction between Nrf2 and NLRP3. Metabonomics revealed that Forsythia suspensa extract significantly improved metabolic function in colitis mice by reversing the abnormal changes in the levels of 9 metabolites. The main metabolic pathways involved were glutathione metabolism, aminoacyl-tRNA biosynthesis and linoleic acid metabolism. In conclusion, we found that Forsythia suspensa extract significantly alleviated DSS-induced UC injury through the Nrf2-NLRP3 pathway and relieved metabolic dysfunction.